Impact of Human Resource Strategy on Service Quality, Sustainable Tourism - Saifuddin, Saifuddin; Bahrunborahima, Bahrunborahima; Novarizcapratiwira, Novarizcapratiwira; Radenhario, Radenhario (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2025)
This research aims to create superior service quality, with continuous training as an important element in developing a skilled, responsive, and customer-oriented workforce. Tourist destinations that prioritize human resource development not only build a positive image and increase competitiveness but also support local economic growth through increased customer loyalty and profitability. Moreover, attention to employee welfare and career development plays a crucial role in improving work morale, workforce retention, and creating a productive work environment. Thus, investment in human resources should be viewed as a strategic long-term strategy to achieve competitive advantage and sustainability for tourist destinations in the face of global competition. This research method uses interviews by analyzing case studies and collecting data from various business actors in the tourism sector to obtain significant results on the relationship between HR strategies, service quality, and sustainable tourism. This study will also use analytical techniques to explain the data collected so as to produce meaningful conclusions. Providing excellent service training (prima) towards a society ready to develop human resources in the growing and sustainable tourism potential. The research results are expected to explain the effectiveness of various HR strategies in the sustainability of service quality in tourism.